ANALYSIS OF DRUG DATA DATA SYSTEMS IN PUSKESMAS SIRAH PULAU PADANG: ANALYSIS OF DRUG DATA DATA SYSTEMS IN PUSKESMAS SIRAH PULAU PADANG - Mir'atul Ramadhani Haidir (International Journal Cister, 2022)
Posyandu iactivities iare ione iof ithe iGovernment's iefforts ito iprovide ihealth iservices ito ithe icommunity. iPosyandu iactivities iare icarried iout iin ithe ivillage iand isupported iby iPosyandu icadres. iIn iBimomartani iVillage iPosyandu iactivities iwere icarried iout iwell iin i12 ihamlets. iHere, iPosyandu iactivities ihave inot ibeen isupported iby iinformation itechnology-based ifacilities. iThis icommunity iservice iactivity iaims ito iimprove ithe icadres' iskills iin iusing iinformation itechnology iapplications ito iimprove ithe iquality iof iservice ito ithe icommunity. iThe imethod iused iis itraining ion ithe iimplementation iof ia iweb-based iand iAndroid-based iPosyandu iInformation iSystem iin iBimomartani iVillage. iThe imain iactivity iof ithis iactivity iis itraining ithe itwo isystems ifor iCadres iand iVillage iMidwives. iThe itraining iresults ifor ithe iAndroid-based iPosyandu iInformation iSystem iare ieasier ito iuse ithan ithe iweb-based iPosyandu iInformation iSystem. iTheir ifrequency iof iusing ia ismartphone icauses ithem ito ibe iskilled iat iusing ismartphones irather ithan iusing ilaptops, ibecause i92% iof icadres iare ihousewives. iExperience ias ia iPosyandu iCadre ialso iincreases ithe ispeed iof icadres iin iusing ithe iPosyandu iInformation iSystem. iCadres iwho ihave imore ithan i5 iyears iexperience iare ieasily iresponsive iin iproviding idata iinput ifor ieach iitem ithat imust ibe ifilled. iBased ion iinput ifrom iCadres iand iMidwives, iadditional ifeatures iare ineeded ion ithis isystem. iThis iis iin iaccordance iwith ithe iinformation ineeds ito ibeadjusted ito ithe ilatest iinformation ineeds. iThe iteam's icommitment ito icontinue ito idevelop ithis isystem iis ineeded iby imost iof ithem ineed iinformation ion imaternal, ichild iand ifamily ihealth ifrom itime ito itime. iIn igeneral, ithe iPosyandu iInformation iSystem iassists iCadres iin istoring idata iand imaking imaternal iand ichild ihealth ireports.